Agricultura regenerativa sustentable para promover la diversidad en el suelo - Meneses Bravo, Marcos Javier (2023)
Sustainable regenerative agriculture is a holistic and conscious approach to agricultural land management that seeks to improve soil health, biodiversity and the resilience of agricultural ecosystems, while ensuring food production is sustainable over the long term. It focuses on restoring and improving soil fertility, conserving natural resources and promoting agricultural practices that are beneficial to both the environment and local farmers and communities. Today we face an ecological situation that is not new. Regenerative agriculture has acquired increasing importance in the fight against climate change and natural resources. Firstly, this form of agriculture focuses on improving and restoring soil health, which leads to greater water and nutrient holding capacity. By employing practices such as crop rotation, the use of organic fertilizers and direct sowing, soil degradation is avoided and natural regeneration is promoted. Healthy soil is vital to maintaining long-term productivity, ensuring food security and reducing the need to expand agricultural areas at the expense of natural ecosystems. Soil degradation can be reversed with organic fertilizers, microorganisms, chemicals, nutrients such as macro and micronutrients that are vital, and the use of green manures and fertilizers such as bioenzymes, which contribute to bacterial life. on earth. Incorporating mycorrhizas, microorganisms, humus, organic solid fertilizers, plantation stubble that provides nutrients as they decompose, another way to reverse damage to the soil is to use plants that, through their development, help cover and compete with weeds.